PERSEPSI DAN PENGETAHUAN ATLET ATLETIK PERSATUAN ATLETIK SELURUH INDONESIA (PASI) JAWA TIMUR TENTANG PENANGANAN CEDERA - Pembayun, Nur Shanti Retno; Wahjuni, Endang Sri; Kumaat, Noortje Anita; Widodo, Achmad; Ayubi, Novadri; Nurhasan, Nurhasan; Al Ardha, Muchamad Arif; Ristanto, Kolektus Oky; Bikalawan, Sauqi Sawa; Panenggak, Nur Syahadati Retno; Ristiawan, Bayu (Journal of Sport and Exercise Science, 2023)
Incidents of injuries that were experienced by track and field athletes in training and matches that are not handled properly. As a result, injury recovery is not always ideal, putting athletes at risk for more serious injuries. This study aims to evaluate the types and treatment of injuries that occur in athletes from the Indonesian Athletics Association (PASI) in East Java Province. This research was conducted in cross-sectional with descriptive and comparative data analysis methods. There were 141 athletic athletes aged 17.97 ± 2.314 years participated in this study. Different test analysis was carried out based on gender, age, and number of competitions that were followed. The instrument used is a questionnaire whose statement items have been tested for validity using Pearson Product Moment and show valid results (p-value <0.05). The results of the normality test showed that the data did not have a normal distribution (p-value <0.05). The non-parametric test showed no significant differences in the perception of injury management based on gender, age, and match number (p-value > 0.05). Furthermore, on the athlete's knowledge, the majority of athletes still believe in traditional handling and do not know first aid for injuries using the Rest, Ice, Compression and Elevation (RICE) method.